Prevalence of contagious caprine pleuro-pneumonia in pastoral flocks of goats in the Rift Valley region of Kenya - Kipronoh, A.K.; Ombui, J.N.; Kiara, Henry K.; Binepal, Y.S.; Gitonga, E.; Wesonga, H.O. (Springer, 2016)
A cross-sectional survey was conducted between the months of March 2014 and March 2015 to determine the prevalence of contagious caprine pleuropneumonia in goat populations in pastoral flocks in three sub-counties of the Rift Valley region. A total of 432 serum samples were collected from goats from 54 flocks and tested for the presence of antibodies against mycoplasma capricolum subspeciescapripneumoniae (mccp) using monoclonal antibody-based competitive enzyme-linked immuno-sorbent assay. Sero-prevalence recorded for Turkana West was 63.9 %, Kajiado Central was 48.6 %, while Pokot East was 29.2 % which was statistically significant (χ2 = 34.997; P = 0.000) in the study sites. The results of this study confirmed that CCPP is widespread and endemic in the pastoral production systems studied in the Rift Valley region. The results confirmed that regions sharing international boundaries are at a higher risk of CCPP hence the need for a unified cross-border approach to disease control measures in the border areas.